Consumers’ Attitudes Related to Biofuel Use in Transportation - Mariasiu, Florin (International Review of Management and Marketing, 2012)
This paper presents the results of a field survey to determine the attitudes of consumers (citizens) related to the use of biofuels in transport. Attitudes of citizens towards biotechnologies and renewable energy use to reduce pollutant effects on the environment are an important factor (and even decisive) in political decision-making necessary to develop new investments and the practical implementation of the proposed projects in the field of renewable sources. The aim of the study was to identify the attitudes of citizens (consumers) regarding follow specific issues: the identification of environmental attitudes and use of biofuels, exploring the connections between attitudes and actions declared effective environmentally taken and exploring attitudes towards authorities environmental policies. It was found that there is a favorable attitude for a massive use of biofuels in transport, even in the absence of relevant sources of information about the complexity of the effects of using biofuels in transport. Keywords: consumer’s attitude; survey; biofuels; transportation; environment. JEL Classifications: C83; D12; L91; Q42